2017
DOI: 10.1200/jco.2017.35.15_suppl.e17593
|View full text |Cite
|
Sign up to set email alerts
|

US-guided percutaneous radiofrequency versus microwave ablation for benign thyroid nodules: A prospective multicenter study.

Abstract: Compared with microwave ablation (MWA), percutaneous radiofrequency ablation (RFA) and laser ablation (LA) have been recommended as minimally invasive treatments for patients with symptomatic benign thyroid nodules (BTNs) because of the large number of clinical applications. This prospective multicenter study sought to evaluate the clinical outcomes of RFA and MWA for BTNs. In eight participating institutions, the total number of 1252 patients treated by RFA and MWA were 649 ones with 687 BTNs and 603 ones wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…Although complete ablation could be achieved in all patients because the large sizes of the nodules, the volumes of nodules were reduced, and the patients' symptoms were relieved significantly at the 3-month follow-up. The 3-month VRR of the nodules was 66.7% AE 7.1%, which was close to the results from the latest studies 16,17,23 focusing on MWA for benign thyroid nodules. However, the initial nodule volumes in those studies were less than 15 mL.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although complete ablation could be achieved in all patients because the large sizes of the nodules, the volumes of nodules were reduced, and the patients' symptoms were relieved significantly at the 3-month follow-up. The 3-month VRR of the nodules was 66.7% AE 7.1%, which was close to the results from the latest studies 16,17,23 focusing on MWA for benign thyroid nodules. However, the initial nodule volumes in those studies were less than 15 mL.…”
Section: Discussionsupporting
confidence: 87%
“…In view of the paucity of clinical research on thermal ablation for SSG, we conducted this prospective study. On the base of our previous experience with MWA for thyroid nodules, 23,25 we conducted this study with rigid inclusion criteria, elaborately planned the treatment protocol, and preliminarily explored the feasibility and safety of MWA in treating SSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The body of evidence on the use of MWA is smaller than that for LA and RFA. However, the published retrospective trials, meta-analyses and multicentre prospective studies demonstrated encouraging results (12-month volume reduction ratio of 75-90%), although the treated nodules were usually small (< 10 mL) [13,40,41].…”
Section: Solid Nodulesmentioning
confidence: 99%